Postoperative delirium is a risk factor of institutionalization after hip fracture: an observational cohort study - Labaste, François; Delort, François; Ferré, Fabrice; Bounes, Fanny; Reina, Nicolas; Valet, Philippe; Dray, Cédric; Minville, Vincent (Frontiers in Medicine, 2023)
Introduction: Hip fracture is a common clinical problem in geriatric patients often associated with poor postoperative outcomes. Postoperative delirium (POD) and postoperative neurocognitive disorders (NCD) are particularly frequent. The consequences of these disorders on postoperative recovery and autonomy are not fully describe. Aim was to determine the role of POD and NCD on the need of institutionalization at 3 months after hip fracture surgery. Method: Population-based prospective cohort study of hip fracture patients between March 2016 and March 2018. The baseline interview, which include a Mini-Mental StateExamination (MMSE), was done in the hospital after admission for hip fracture. NCD was appreciated by MMSE scoring evolution (difference between preoperative MMSE and MMSE at day 5 greater than 2 points). POD was evaluated by Confusion Assessment Method. The primary endpoint was the rate of new institutionalization at 3 months. We used a multivariate analysis to assess the risk of new institutionalization.Results: A total of 63 patients were included. Thirteen patients (20,6%) were newly institutionalized 3 months. Two factors were significatively associated with the risk of postoperative institutionalization at 3 months: POD